Comparative midrib anatomy of Monodora Dunal. and Isolona Engl. (Annonaceae) from West-central Africa (Bangladesh Journal of Plant Taxonomy, 2020)
This article assessed midrib anatomical description of Isolona Dunal. And Monodora Engl. (Annonaceae) from West-Central Africa. Twelve species of tribe Monodoreae were investigated on the basis of micromorphology of midrib characters with the aid of light microscopy. The study provided important taxonomic characters which aid delineation of inter and infrageneric species within the duo genera. The generic features include centrally positioned, open collateral vascular bundle and furrow shaped midribs which are diagnostic to the genera.U shaped vascular bundles are present in most of the species with inviginating or expanded endings while marginal traces vary from 2 to 4. The presence of keel protrusion at abaxial surface established a closer affinity among M. angolensis, M. crispata, and M undulata with additional features species were delimited. Other variable useful features of midrib encountered are trichomes, parenchyma, collenchyma and sclerenchyma, and adaxial and abaxial shape. The midrib characters have been used to prepare an indented dichotomous key to delimit the species in the genera studied.Bangladesh J. Plant Taxon. 27(2): 283-291, 2020 (December)